Rise trend and growth of our nation - Wickman, Daniel F. (My University, 1892)
Introduction: Nations do not grow as in olden times slowly and silently like the sturdy oak of the forest, but deafen the ears of the cool observer with the roar of their sudden uprising. Proceeding nations lived half their life before they reached any degree of maturity. Rome was a babe for 1000 years. Japan and China have for thousands of years been nursed in the lap of time and today they do not show marks of advancement that characterized America a century ago. Contrast if you will the countries of Greece Phoenicia, and Egypt with that of our own new America. It took ten centuries for Greece to attain her boastful superiority. Egypt and Phoenicia lived for 2000 years to reach but the shadow of the advancement of that of our own delightful country. Can we not then with a feeling of pride boast of our rapid progress. Think for the moment—300 year ago no settler had ever set foot on American soil. Can you place yourselves in those days. Picture yourselves in company with that body of abused and persecuted but fearless pilgrims planning in the cabin of the Mayflower a code of laws for mutual strength and protection.
Citation: Wickman, Daniel F. Rise trend and growth of our nation. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Nation; Civilization; Colonialization; America; Development; History; Theses; Manuscripts (documents)